Análisis filogenético de Neorickettsia risticii detectada en murciélagos de Argentina - Cicuttin, G.L. (2016)
Potomac horse fever (equine monocytic ehrlichiosis) is caused by Neorickettsia risticii (formerly Ehrlichia risticii), with clinical cases reported only in the USA, Brazil and Uruguay. N. risticii is an endosymbiont of flukes with a complex life cycle utilizing various hosts such as aquatic snails and arthropods, and vertebrate insectivores. Different phylogenetic studies revealed that N. risticii consists of various strains in the USA, but no information is available from Brazil and Uruguay. In our country, N. risticii was first detected in 2013 in Tadarida brasiliensis bats from Buenos Aires city\n(CABA). The aim of our study was to characterize phylogenetically N. risticii detected in CABA. The three DNA samples previously obtained were positive by nested-PCR for a fragment of 16S rRNA of Neorickettsia genus and were sequenced, resulting in a 100% similarity among them and 99.5 to 99.7% with various strains of N. risticii from USA. Only one sample could be amplified by nested-PCR for a fragment of groESL gene. Phylogenetic analysis revealed that the current strain is related to strains of N. risticii along the west coast of the USA. Given the potential impact of veterinary medicine, molecular characterization of N. risticii circulating in South America is of great importance. In addition, the circulation of this pathogen in our country requires additional studies to understand the ecology and transmission of N. risticii, and detecting the occurrence of equine cases.\n